357 Human Milk Bile Salt-Stimulated Lipase: the Dynamic Changes During Lactation. (October 2012) - Piemontese, P; Roncada, P; Soggiu, A; Bonizzi, L; Budelli, A; Agostoni, C; Giannì, ML; Roggero, P; Mosca, F
Abstract : Background and Aims: The efficient digestion of milk triglycerides is guaranteed by the combined action of gastric lipase, colipase-dependent pancreatic lipase, and bile salt-stimulated lipase (BSSL). Human milk contains the major part of BSSL. Data regarding the dynamic changes of human milk BSSL are scarce. The aim of this study was to evaluate the changes of human milk BSSL content at different stages of lactation by proteomic techniques. Methods: We designed a prospective longitudinal study. Human milk samples were collected from 18 healthy mothers who delivered a singleton term newborn (Gestational age 37–41 weeks) on the 3 th, 7 th, 15 th, and 60 th postpartum day. Proteomic techniques were carried out to evaluate different profile expression of BSSL in milk: in particular SDS-PAGE analysis coupled with LC-MS MS mass spectrometry. Results: BSSL levels increased significantly from the 3 th to the 60 th postpartum day (figure ). Conclusions: The increased levels of human milk BSSL could compensate for low endogenous capacity to digest dietary fat in early life as efficient absorption of lipids is important, not only for energy utilization but also for optimal growth and functional neurodevelopment.